The Association of Low Birth Weight and the Incidence of Stunting among Under-Fives in Indonesia: A Systematic Review - Safhira, Bella; Anggraini, Junisa; Tarina, Lian; Apriani, Sasmita; Budiastuti, Anggun; Pulungan, Rafiah Maharani; Muharramah, Disa Hijratul (Jurnal Ilmiah Kesehatan Masyarakat : Media Komunikasi Komunitas Kesehatan Masyarakat, 2025)
Abstract Background: Stunting or failure to thrive in children is characterized by lower height compared to the child's age standard. Stunting in children under five not only affects their physical and cognitive development, but also impacts their future quality of life. LBW is one of the factors that increase the risk of stunting. This study aimed to examine the association between low birth weight (LBW) and the prevalence of stunting in children under five through a systematic review. Method: The search for scientific articles of case-control analytic observational studies with research locations in Indonesia from 2020 to 2024 was conducted through two databases, namely Semantic Scholar and Google Scholar using Harzing's Publish or Perish application. This systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines with study quality assessment using The JBI Critical Appraisal Checklist for Case-Control Study. Result: From a total of 63 articles obtained, 13 articles were extracted after going through a screening process based on inclusion criteria, exclusion criteria and article quality assessment. Of the 13 studies, 10 studies or 77%, concluded that LBW had an association with stunting. Conclusion: Based on a systematic review, LBW is one of the important risk factors contributing to stunting among children under five in Indonesia. Therefore, interventions that focus on improving maternal nutrition and education on maternal health before, during, and after pregnancy are very important to be maximized to reduce and minimize the incidence of LBW and prevent stunting.